2014
DOI: 10.1177/0961000613518572
|View full text |Cite
|
Sign up to set email alerts
|

How do libraries manage the ethical and privacy issues of RFID implementation? A qualitative investigation into the decision-making processes of ten libraries

Abstract: http://www.canberra.edu.au/researchrepository/items/0d1d7911-7fa6-4d38-a762-7ee9c1d0db39/1/ Copyright: ©2014 The Authors Version:This is the authors' peer reviewed version of a work that was accepted for publication in the Australian Journal of Librarianship and Information Science which has been published at http://doi.org/10.1177/0961000613518572 . Changes resulting from the publishing process may not be reflected in this document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…This mirrors previous work on how LIS professionals deal with the potential issues of ICT where we found that often these issues were referred 'upwards' through the organisational hierarchy rather than dealt with using library codes of ethics (Ferguson et al, 2015). This awareness of ethics, combined with lack of detailed knowledge of codes of ethics, is echoed by Senapatiratne (2013) who found that librarians could perceive ethical dilemmas between the codes of ethics and institutional guidelines, when a more detailed examination of them both would have shown no conflict.…”
Section: What Resources Do Lis Professionals Consult To Assist Ethicasupporting
confidence: 69%
See 1 more Smart Citation
“…This mirrors previous work on how LIS professionals deal with the potential issues of ICT where we found that often these issues were referred 'upwards' through the organisational hierarchy rather than dealt with using library codes of ethics (Ferguson et al, 2015). This awareness of ethics, combined with lack of detailed knowledge of codes of ethics, is echoed by Senapatiratne (2013) who found that librarians could perceive ethical dilemmas between the codes of ethics and institutional guidelines, when a more detailed examination of them both would have shown no conflict.…”
Section: What Resources Do Lis Professionals Consult To Assist Ethicasupporting
confidence: 69%
“…This paper develops previous work which concluded that ethical dilemmas exist within the library and information services (LIS) sector (Thornley et al, 2011) but that ethical concerns may not be particularly important for all library and systems managers when they implement new technologies (Ferguson et al, 2015). Libraries and related agencies are vital for disseminating information to a wide audience, and developments in Information and Communication Technologies (ICTs) are transforming how this information is processed and accessed.…”
Section: Introductionmentioning
confidence: 99%
“…First, there are implications for user privacy. Networked technologies such as cloud-based services and library websites may track users or otherwise collect user data (Kritikos and Zimmer 2017;O'Brien et al 2018) and physical technologies such as RFID technology, laptops, scanners, and self-checkout machines pose challenges regarding data and network security, workstation security, and intellectual property (Nichols Hess, LaPorte-Fiori, and Engwall 2015;Ferguson, Thornley, and Gibb 2015). During 2015-2016, the Intellectual Freedom Committee of the American Library Association (ALA) produced guidelines documents (ALA 2016b) and privacy checklists (ALA 2016a) to support patron privacy in libraries, including in the areas of E-book Lending and Digital Content Vendors; Data Exchange Between Networked Devices and Services; Public Access Computers and Networks; Library Websites, OPACs, and Discovery Services; and Library Management Systems.…”
Section: Technology Services In Librariesmentioning
confidence: 99%
“…First, there are implications for user privacy. Networked technologies such as cloud-based services and library websites may track users or otherwise collect user data (Kritikos and Zimmer 2017;O'Brien et al 2018) and physical technologies such as RFID technology, laptops, scanners, and self-checkout machines pose challenges regarding data and network security, workstation security, and intellectual property (Nichols Hess, LaPorte-Fiori, and Engwall 2015;Ferguson, Thornley, and Gibb 2015). During 2015-2016, the Intellectual Freedom Committee of the American Library Association (ALA) produced guidelines documents (ALA 2016b) and privacy checklists (ALA 2016a) to support patron privacy in libraries, including in the areas of E-book Lending and Digital Content Vendors; Data Exchange Between Networked Devices and Services; Public Access Computers and Networks; Library Websites, OPACs, and Discovery Services; and Library Management Systems.…”
Section: Technology Services In Librariesmentioning
confidence: 99%